Communists and community : activism in Detroit's labor movement, 1941-1956 - Pettengill, Ryan S., 1980- (Temple University Press, 2020)
"Communists and Community chronicles labor activism and community organizing sponsored by the Communist Party in Detroit from 1942 to 1956, to investigate the changing nature of community-based activism in the twentieth century"--